2018
DOI: 10.1080/02701960.2018.1469488
|View full text |Cite
|
Sign up to set email alerts
|

Older people’s adoption of e-learning services: A qualitative study of facilitators and barriers

Abstract: This research investigates the facilitators and barriers for older people to adopt e-learning services using qualitative data of older people in a Chinese city. A qualitative approach was applied to explore the perceived facilitators and obstacles toward e-learning adoption with 10 older Chinese aged over 50. The results indicate the following: (1a) Age-related changes and cohort effects were found to be the internal barriers for the adoption of e-learning. (1b) Equipment problems, lack of time, and the availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
1
14
0
1
Order By: Relevance
“…Ali et al, (2018) identified 68 unique e-learning barriers like, language, setupcosts, absence of real-time feedback, course-content, pedagogy, student-readiness, computerliteracy, technological difficulty, prior knowledge, technical support, etc. Bai et al, (2018) in a qualitative study on Chinese people, found that technological barriers (equipment and adaptability) had a negative influence on adoption of online-courses. Additionally, flexibility and user-interface affected intention-to-use.…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…Ali et al, (2018) identified 68 unique e-learning barriers like, language, setupcosts, absence of real-time feedback, course-content, pedagogy, student-readiness, computerliteracy, technological difficulty, prior knowledge, technical support, etc. Bai et al, (2018) in a qualitative study on Chinese people, found that technological barriers (equipment and adaptability) had a negative influence on adoption of online-courses. Additionally, flexibility and user-interface affected intention-to-use.…”
Section: 1mentioning
confidence: 99%
“…Additionally, choosing a good course from a mediocre one is a confusing task due to the large number of online courses present in e-Learning platforms . Although earlier researchers in the e-Learning domain has attempted at exploring the barriers that affect adoption of e-Learning services qualitatively (Oomen-Early and Murphy, 2009;Bai, He, and Kohlbacher, 2018) as well as quantitatively (Al Gamdi and Samarji, 2016;Ali et al, 2018), researchers have noted that qualitative and quantitative techniques suffer from limitations related to sample size and the population spread (Boddy, 2016;Simmons, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Tertiary institutions are therefore obliged to respond to digitalised technology demands to equip students with 4th IR skills and competencies for the labour markets, thus requiring changes in the BE education (Bai et al, 2020;Philips 2017;Bates, 2016;Jacobs 2015). Inefficiencies that manifests in delays in planning, building and construction processes that cause cost and schedule overruns and further impact on efficiency and productivity in the BE industry are gradually being addressed, and the 4th IR education is being propagated as a partial way out.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The increasing inadequacy in knowledge and skill acquisition of 4th IR and innovative digitalised concepts among most lecturers and students alike directly reflects in the inefficient, imprudent execution and implementation of projects -by modern standards -in the BE industry (Jacobs 2015). These inadequacies are attributed to a lack in corresponding, relevant education that is needed to unlock the potential in BE professionals via education, and seen as a major barrier to progress (Bai et al, 2020;Bates, 2016;Jacobs;2015;Shafii, Ali & Othman, 2006). Designers, Construction engineers and property developers often make decisions that impact on the environment and society (Clevenger et al, 2017) and ability to make well-informed, holistically viable contributions depends on the type of acquired knowledge that informs them.…”
Section: Challenges Of 4th Ir Incorporation In Built Environment Educationmentioning
confidence: 99%
“…Although studies on the use and adoption of digital technology by older adults have increased in recent years (Chen and Chan, 2014; Ma et al , 2021; Martín-García et al , 2021b; Murciano-Hueso et al , 2022), most publications state that a more in-depth study of how older adults adopt, perceive and use digital technology is necessary (Bai et al , 2020; Martín-García et al , 2021b ; Wanka and Gallistl, 2021).…”
Section: Introductionmentioning
confidence: 99%